A study on foremost scientific writing books for graduate students and faculty members - Sajid Iqbal , Muhammad Ijaz Mairaj , Maliha Saleem , Muhammad Majid Gulzar, (IJoLIS, 2023)
Purpose - Several books on scientific writing and style guides have been published to enable new graduate students and early career researchers in thriving their careers by learning the art of articulating their work. This paper reports the reviews of 10 books on scientific writing and their transaction statistics from the main libraries of selected universities in Pakista